1999
DOI: 10.1002/(sici)1097-4679(199901)55:1<21::aid-jclp2>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and neuropsychological predictors of coping patterns by patients with multiple sclerosis

Abstract: To determine the relative contribution of psychological and neuropsychological (NP) variables to the prediction of patterns of coping with disease-related stressors and satisfaction with their coping efforts, 56 patients with multiple sclerosis (MS) were administered the Ways of Coping Checklist, the Symptom Checklist-90-Revised, and a battery of NP tests chosen for their sensitivity to MS. Higher levels of psychological distress were associated with greater use of emotion-focused coping strategies and reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 14 publications
3
21
0
Order By: Relevance
“…Particularly for the exacerbation group, it was expected that the coping strategies adopted by respondents would predict mood and self-esteem over time. Most previous studies have examined the cross-sectional relationships between coping and adjustment, and so the level of stability in the adjustment variable could not be partialled out in the analyses [10,12]. However, Pakenham [11] did find that better psychological adjustment over a 12-month period among persons with MS was predicted by high levels of problem-focused coping and low levels of emotionfocused coping at Time 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly for the exacerbation group, it was expected that the coping strategies adopted by respondents would predict mood and self-esteem over time. Most previous studies have examined the cross-sectional relationships between coping and adjustment, and so the level of stability in the adjustment variable could not be partialled out in the analyses [10,12]. However, Pakenham [11] did find that better psychological adjustment over a 12-month period among persons with MS was predicted by high levels of problem-focused coping and low levels of emotionfocused coping at Time 1.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of studies that support this proposal. For example, Jean et al [10] found that persons with MS who used more emotion-focused coping strategies (e.g., denial, hoping the problem would just go away) were more likely to experience psychological distress than those who used problem-focused coping strategies (e.g., developing strategies to deal with the situation). Similar results were obtained by both Pakenham [11] and Pakenham et al [12].…”
Section: Introductionmentioning
confidence: 99%
“…In cross-sectional surveys, emotion-focused coping has been related to lower self-esteem [41], global distress [42][43][44], and depression [13,15,[45][46]. Similar results were found in studies that examined the relationship between coping styles and depression over time [47][48].…”
Section: Copingmentioning
confidence: 93%
“…Problemfocused coping has been linked to higher self-esteem [41], global distress [42], and depression [15,45], but other studies have failed to find a correlation [13,[43][44]. Longitudinal studies have sometimes found associations between problem-focused coping and depression.…”
Section: Copingmentioning
confidence: 99%
“…There is also some concern regarding the construct validity of the WCQ because the existing evidence is based primarily on exploratory factor analyses [7]. In recent years, there has been a growing use of the WCQ in clinical settings involving cancer [8,9], multiple sclerosis [10], Parkinson's disease [11], fibromyalgia [12], stroke [13,14], chronic fatigue syndrome [15], and spinal cord injury [16]. As was the case for the studies on healthy subjects, studies performed on patients have not confirmed the construct validity of the WCQ, nor are they in agreement regarding alternative factor structures [8,15,17 -19].…”
Section: Introductionmentioning
confidence: 99%